Does motivation theory really play any significant role on explaining university teachers’ performance: Understanding Bangladeshi context - Sultana, Rebaka; Faruk, Mohammad; Islam , Md. Saiful; Khaled, Md. Asif (Asian Management and Business Review, 2025)
The development of human capital is significantly impacted by the way teachers nurture and expand their students' intellectual capacity. The motivation of teachers is a crucial determinant of their performance, and consequently, it influences the success and achievements of their students. In the context of Bangladesh's tertiary education system, the purpose of this study is to look into the implications of motivational theories on explaining and improving university teachers' performance. Along with the Maslow's and Herzberg's needs theory, there are other motivation theories and this study will investigate the current aspects that affect teachers' performance. A convenience sample of 200 randomly chosen informants is obtained via structured survey. To evaluate the study's hypotheses, factor analysis is used. The results indicate that most instructors in Bangladesh lack intrinsic motivation, which has no visible impact on their performance. Conversely, extrinsic incentive and instructors' performance are positively and significantly correlated. The whole basic wage package seems to have the greatest influence on teachers' motivation among all other elements. Finally, the study recommends that stakeholders should prioritize and enhance incentives, putting an emphasis on sustainable development to raise living standards in rural areas for teachers to boost their level of motivation and performance.